The Influence of Financial Literacy, Money Attitude, and Self-Control on Financial Distress Through Impulsive Buying as a Mediating Variable Among Paylater Users in Surabaya City - Nur Lailatus Sholikha; Nadia Asandimitra Haryono; Harlina Meidiaswati (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of financial literacy, money attitude, and self-control on financial distress through impulsive buying as a mediating variable among Paylater users in Surabaya City. The research was conducted to examine whether financial literacy, money attitude, and self-control significantly affect financial distress directly and indirectly through impulsive buying behavior. The study hypothesizes that higher financial literacy and self-control reduce financial distress, while negative money attitudes and impulsive buying tendencies increase financial distress among Paylater users. This research employed a quantitative approach using a causal associative design. Data were collected through questionnaires distributed to Paylater users in Surabaya City using purposive sampling techniques. The respondents consisted of active users of Paylater services who had experience using digital payment and credit facilities. The collected data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to test the relationships among variables and the mediating effect of impulsive buying. The results indicate that financial literacy and self-control have a negative and significant effect on financial distress, while money attitude and impulsive buying positively influence financial distress. Furthermore, impulsive buying was found to mediate the relationship between financial literacy, money attitude, self-control, and financial distress. Individuals with low financial literacy and weak self-control tend to engage in impulsive buying behavior, which ultimately increases the risk of financial distress. The findings imply that improving financial literacy and strengthening self-control are essential strategies to minimize financial distress among Paylater users. Financial institutions, educational institutions, and policymakers are encouraged to provide financial education programs and promote responsible digital financial behavior. Future studies are recommended to expand the research scope by involving larger populations, additional variables, and different geographical areas to obtain broader insights into consumer financial behavior in the digital era.